Analisis Konsep Good Corporate Governance Dalam Perspektif Syariah Untuk Mengatasi Permasalahan Penerapan Corporate Governance Perbankan Di Indonesia - M. Iqbal; Basania Nasution; Dina Maharani; Khairan Tuahdi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Good Corporate Governance is the most well-known principle in the world for maintaining the integrity of world organizations. Almost all international locations in all countries adhere to the foundation of building responsibility and openness. Unfortunately, in its application, GCG does not explain the values ​​of stakeholders. The study aims to reconstruct GCG (OECD version) and look for a more appropriate Sharia Concept. Of course, this will provide a solution to the problem itself. After analyzing the values ​​and character of SET, we built a modern GCG positioned on Islamic concepts. These concepts are; One; deeper sympathy from stakeholders, second; principles regarding stakeholder rights: third, equality in stakeholder behavior, fourth, the principle of openness, finally, regarding corporate accountability.Weak GCG practices in Indonesia are caused by the low level of protection for investors, law enforcement, transparency and ineffective public company audit committees. This condition strongly encourages the need for effective and efficient global corporate governance. Islamic Corporate Governance The Islamic perspective lies in the Islamic Company Theory which has greater concern for wider stakeholders which include God, humans and nature. The difference in goals between conventional Corporate Governance and Sharia GCG which tends to adhere to Sharia Enterprise Theory (SET). SET equates material and spiritual values. This shows that Sharia GCG does not only achieve material benefits, but also spiritual values. SET also equates egoistic values ​​with altruistic values, which in Islamic law are realized in the form of worship.